Representation of violence in relationships in It Ends With Us movie: a contemporary feminist study - Winarsih, Anis Dwi; Yustisia, Karlina Karadila (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2024)
This study aims to analyze the representation of violence in romantic relationships shown in the film *It Ends With Us* through the perspective of contemporary feminism. The focus of this study is how forms of violence, both physical and emotional, are represented and how the film reflects or challenges patriarchal values that are still dominant in interpersonal relationships. The research method used is textual analysis with a qualitative approach, referring to contemporary feminism theories that highlight issues of power, gender, and women's agency. The results show that the movie depicts relationship violence as a complex experience that is often wrapped up in the dynamics of love and forgiveness. Furthermore, the film features the main female character's struggle to redefine her position as an empowered individual in the midst of an oppressive situation. The findings make an important contribution to the discourse on critical awareness of gender-based violence in popular media and its relevance to contemporary feminist struggles.